Perturbations of Polynomials with Operator Coefficients. (24th March 2013) - Gil', Michael
Abstract : We consider polynomials whose coefficients are operators belonging to the Schatten-von Neumann ideals of compact operators in a Hilbert space. Bounds for the spectra of perturbed pencils are established. Applications to differential and difference equations are also discussed.